Transparency. Issue 4 (18th May 2016) - Farrell, Maggie
ABSTRACT: Within organizations, employees often discuss the need for transparency but what exactly is transparency? Transparency is often linked with communication in an effort to create an organization that is more informed about decisions and processes creating a sense of employee engagement. But leaders are not able to operate in a completely open manner due to a variety of factors. What leadership activities can be conducted in a transparent manner and how is transparency balanced with confidentiality? Transparency is not just a leader responsibility but other managers and employees contribute to organizational transparency. This column will provide more insights into the complex issue of transparency within libraries.